2022
DOI: 10.1186/s13019-022-01801-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of costal cartilage fractures with titanium plate internal fixation

Abstract: Background This study aim to evaluate surgical procedures for titanium plate internal fixation of costal cartilage fractures with displacement or nonunion. Methods From January 2019 to October 2020, 13 patients with costal cartilage fractures were treated with titanium plate internal fixation in the thoracic surgery department of the Shanghai Sixth People’s Hospital. Pain severity scale scores and respiratory function were evaluated preoperatively … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…With multiple nonunions and dislocations resulting essentially in a flail segment, his symptoms were unsurprising. Similar cases have been described in which patients suffering from multiple thoracic injuries underwent operative fixation with improved outcomes after reconstruction of rib fractures, costosternal nonunions, and costal cartilage fractures 3,5,13-15,18 . Surgical reconstruction of flail chest pathology has also demonstrated improvements in postoperative pulmonary function 19 .…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…With multiple nonunions and dislocations resulting essentially in a flail segment, his symptoms were unsurprising. Similar cases have been described in which patients suffering from multiple thoracic injuries underwent operative fixation with improved outcomes after reconstruction of rib fractures, costosternal nonunions, and costal cartilage fractures 3,5,13-15,18 . Surgical reconstruction of flail chest pathology has also demonstrated improvements in postoperative pulmonary function 19 .…”
Section: Discussionsupporting
confidence: 54%
“…In cases of multiple rib fractures, sternal fractures, and flail chest, studies have confirmed that operative fixation can result in improved pain and faster return to function 1,2,4,5,17 . Approximately 7% of all rib fracture admissions are actually misdiagnosed as costal cartilage fractures 3,10 . Furthermore, costal cartilage fractures may involve the lower costal margin or costosternal junction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations